(untitled) (Communications in Computational Physics, 2010)
Thanks to the Cagniard-de Hoop's method we derive the solution to the problem of wave propagation in an infinite bilayered acoustic/poroelastic media, where the poroelastic layer is modelled by the biphasic Biot's model. This first part is dedicated to solution to the two-dimensional problem. We illustrate the properties of the solution, which will be used to validate a numerical code.